Controlled co-delivery system of magnesium and lanthanum ions for vascularized bone regeneration. (15th October 2021) - Luo, Ruochen; Huang, Yiqian; Yuan, Xiaojing; Yuan, Zuoying; Zhang, Liwen; Han, Janming; Zhao, Yuming; Cai, Qing
Abstract: For craniofacial bone regeneration, how to promote vascularized bone regeneration is still a significant problem, and the controlled release of trace elements vital to osteogenesis has attracted attention. In this study, an ion co-delivery system was developed to promote angiogenesis and osteogenesis. Magnesium ions (Mg 2+ ) and lanthanum ions (La 3+ ) were selected as biosignal molecules because Mg 2+ can promote angiogenesis and both of them can enhance bone formation. Microspheres made of poly(lactide-co-glycolide) were applied to load La2 (CO3 )3, which was embedded into a MgO/MgCO3 -loaded cryogel made of photocrosslinkable gelatin methacryloyl to enable co-delivery of Mg 2+ and La 3+ . Evaluations of angiogenesis and osteogenesis were conducted via both in vitro cell culture using human bone marrow mesenchymal stromal cells and in vivo implantation using a rat model with calvarial defect (5 mm in diameter). Compared to systems releasing only Mg 2+ or La 3+, the combination system demonstrated more significant effects on blood vessels formation, thereby promoting the regeneration of vascularized bone tissue. At 8 weeks post-implantation, the new bone volume/total bone volume ratio reached a value of 40.1 ± 0.9%. In summary, a properly designed scaffold system with the capacity to release ions of different bioactivities in a desired pattern can be a promising strategy to meet vascularized bone regeneration requirements.